Graph-Based Representations in Pattern Recognition 9th IAPR-TC-15 International Workshop, GbRPR 2013, Vienna, Austria, May 15-17, 2013. Proceedings - Kropatsch, Walter G.; Artner, Nicole M.; Haxhimusa, Yll.; Jiang, Xiaoyi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 9th IAPR-TC-15 International Workshop on Graph-Based Representations in Pattern Recognition, GbRPR 2013, held in Vienna, Austria, in May 2013. The 24 papers presented in this volume were carefully reviewed and selected from 27 submissions. They are organized in topical sections named: finding subregions in graphs; graph matching; classification; graph kernels; properties of graphs; topology; graph representations, segmentation and shape; and search in graphs.
A One Hour Trip in the World of Graphs, Looking at the Papers of the Last Ten Years -- A Unified Framework for Strengthening Topological Node Features and Its Application to Subgraph Isomorphism Detection -- On the Complexity of Submap Isomorphism -- Flooding Edge Weighted Graphs -- Graph Matching with Nonnegative Sparse Model -- TurboTensors for Entropic Image Comparison -- Active-Learning Query Strategies Applied to Select a Graph Node Given a Graph Labelling -- GMTE: A Tool for Graph Transformation and Exact/Inexact Graph Matching -- A Comparison of Explicit and Implicit Graph Embedding Methods for Pattern Recognition -- Adjunctions on the Lattice of Dendrograms -- A Continuous-Time Quantum Walk Kernel for Unattributed Graphs -- Relevant Cycle Hypergraph Representation for Molecules -- A Quantum Jensen-Shannon Graph Kernel Using the Continuous-Time Quantum Walk -- Treelet Kernel Incorporating Chiral Information -- A Novel Software Toolkit for Graph Edit Distance Computation -- Map Edit Distance vs. Graph Edit Distance for Matching Images -- An Algorithm for Maximum Common Subgraph of Planar Triangulation Graphs -- Graph Characteristics from the Schrödinger Operator -- Persistent Homology in Image Processing -- Towards Minimal Barcodes -- A Fast Matching Algorithm for Graph-Based Handwriting Recognition -- On the Evaluation of Graph Centrality for Shape Matching -- Shape Recognition as a Constraint Satisfaction Problem -- Gaussian Wave Packet on a Graph -- Exact Computation of Median Surfaces Using Optimal 3D Graph Search -- Estimation of Distribution Algorithm for the Max-Cut Problem.
Keywords: Computer science; Data structures (Computer science).; Computational complexity; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Pattern Recognition; Image Processing and Computer Vision; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Graphics; Discrete Mathematics in Computer Science; Data Structures